The glycosylated hemoglobin level and the severity of cardiovascular involvement in patients with the first episode of acute coronary syndrome - Saman Khaleghi; Mohammadali Bayani; Naghmeh Ziaei; Mohammadtaghi Salehiomran; Soraya Khafri (Babol University of Medical Sciences, 2024)
Background: The current study was carried out aiming at investigating the relationship between glycosylated hemoglobin level and coronary atherosclerosis in patients with the first episode of acute coronary syndrome. Methods: This case-control study evaluated 450 patients with the first episode of acute coronary syndrome in Ayatollah Rouhani Hospital in Babol (Iran) from 2011 to 2018. Based on glycosylated hemoglobin, patients were divided into three groups of non-diabetic, pre-diabetic, and diabetic (n=150 in each group). Since SYNTAX score and Gensini score are employed to evaluate the extent of cardiovascular disease and predict CVD in patients with CAD over long-term follow-up, we calculated SYNTAX score and Gensini score based on angiographic results. Results: Concerning the factors related to the severity of cardiovascular involvement, the results revealed no significant difference between the diabetic and pre-diabetic groups in terms of the frequency of patients in terms of SYNTAX score, Gensini score, and the number of vessels involved (0.142 and 87, respectively, and P=0.102). However, this difference between the diabetic and non-diabetic groups, as well as between the pre-diabetic and non-diabetic groups was statistically significant (respectively for SYNTAX score, p< 0.001 and P=0.001; for Gensini score, P=0.013 and P=0.019; and for the number of vessels involved P=0.001and p<0.001). Conclusion: According to the findings of the current study, since there was no significant difference between diabetic and pre-diabetic patients in terms of the components indicating the severity of cardiovascular involvement, pre-diabetes itself may be associated with the severity of cardiovascular involvement as a predisposing factor.